Estrategias de prevención de tuberculosis pulmonar en pacientes adultos con VIH - Aguay Pintado, Johnny Andrés (2025)
Tuberculosis is a common infection in HIV patients, causing increased costs, prolonged treatment and multidrug resistance. This led to the search for prevention strategies that would reduce tuberculosis co-infection in HIV patients through a systematic review of the literature. Here, the PICO query and a search strategy using MeSH terms and Boolean operators were used. For the capture of scientific articles, the PRISMA strategy was used in PUBMED and COCHRANE. As a result, 37 studies were obtained, which were analyzed. The results obtained were that the prevention strategy that had the greatest impact on the reduction of tuberculosis co- infection in HIV patients was the administration of prophylactic antituberculosis treatment based on isoniazid as monotherapy for a minimum of 6 months at a daily dose and combined therapy with rifampicin for 6 months at a daily dose. In addition, the application of the WHO W4SS strategy, added to diagnostic methods such as C-reactive protein or chest x-ray, should be used as diagnostic suspicion methods. Subsequently, the application of confirmatory tuberculosis tests such as bacilloscopy is suggested. Of these, Xpert is considered the gold standard method for confirming tuberculosis, since it provides a resistance profile to isoniazid and rifampicin, providing a guide for the start of treatment, especially for cases resistant to these drugs. Although no evidence was found on the administration of Vitamin D3 as a sole strategy to prevent tuberculosis, future studies should be carried out combining prevention strategies and evidencing future benefits